Does thermodynamics rule out the existence of cosmological singularities? - Schiffer, Marcelo (Springer Nature, 1991)
Recently, Bekenstein showed that a singularity in the FRW radiation-dominated cosmological model is inconsistent with the entropy bound, a new thermodynamic law he put forward a few years ago. In this paper we generalize his results and show that, regardless of model peculiarities, the existence of cosmological singularities is incompatible with thermodynamics. © 1991 Plenum Publishing Corporation.